DNA Reaction Network Mimicking the Basic Steps of Synaptic Communication. Issue 11 (22nd March 2023) - Hu, Minghao; Hu, Yuqiang; Yuan, Wenqian; Zhang, Zhen; Wu, Tongbo
Comprehensive Summary: Biological systems use intricate networks of chemical reactions to exchange information. How to simulate complex systems with simple strand‐displacement reactions is crucial to broaden the application scenario of the DNA reaction network. Here, we report the artificial DNA reaction network to mimic the operation and function of biological information transfer via strand‐displacement reaction. DNA is used as simple artificial analogs to schematize structures and transmit information. Using chemical synapses in neural networks as an example, we show that the proposed network enables core functions of biological systems, such as the long‐term potential of synapses, which underpin learning and memory. Also, we performed the simple "silicon mimetic" to link electronic circuits to chemical network‐based biological structures. As such, synaptic communication simulated by the DNA reaction network provides a complete demonstration for designing artificial reaction networks based on the essence of information interaction. Abstract : We developed a DNA reaction network mimicking synaptic communication, and silico simulations were performed to link multi‐domain systems engineering.